A PC / PET alloy material and preparation method thereof

By using talc powder with specific pH and acrylonitrile-styrene-acrylic acid copolymers in PC/PET alloy materials, the problems of poor compatibility and poor thermal stability of PC/PET alloy materials are solved, and high heat resistance and stability are achieved and excellent comprehensive performance.

CN118271821BActive Publication Date: 2024-12-17KINGFA SCI & TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410529261.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-29
Publication Date
2024-12-17
Estimated Expiration
2044-04-29

AI Technical Summary

Technical Problem

PC/PET alloy materials have poor compatibility between PC and PET and the presence of reactive groups, resulting in poor thermal stability and appearance performance. Traditional compatibility agents cannot effectively improve their comprehensive performance, especially after the introduction of mineral fillers, the performance further deteriorates. .

Method used

Introduce talc powder with specific pH as reinforcement filler in PC/PET alloy materials, and combine acrylonitrile-styrene-acrylic acid copolymer as reinforcement polymer to improve compatibility and heat resistance, while talc powder as rigidity enhancement Together, it can improve the toughness and appearance performance of the product.

Benefits of technology

It realizes high heat resistance, good appearance and excellent comprehensive performance of PC/PET alloy materials, ensuring the ideal rigidity and toughness requirements of the product, and avoiding the performance degradation after the introduction of mineral fillers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004817640010000071
    Figure BDA0004817640010000071
  • Figure BDA0004817640010000081
    Figure BDA0004817640010000081
  • Figure BDA0004817640010000082
    Figure BDA0004817640010000082
Patent Text Reader

Abstract

The invention discloses a PC / PET alloy material and a preparation method thereof, belonging to the technical field of polymer materials. The product introduces talcum powder with a specific pH value into a matrix resin as a reinforcing filler, and compounded with a special reinforcing polymer as a modified component. The component can not only improve the overall compatibility of the product, but also inhibit the reaction activity of the matrix resin, improve the heat resistance stability and appearance of the product, and can also assist the talcum powder as a rigidity enhancer to improve the rigidity performance of the product under the premise of ensuring sufficient toughness, and the comprehensive performance of the product is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer alloy materials, and in particular to a PC / PET alloy material and a preparation method thereof. Background Art

[0002] PC (polycarbonate) / PET (polyethylene terephthalate) alloy material is a high-performance material that combines the high rigidity and heat resistance of PC with the solvent resistance of PET. In theory, it has a very wide range of applications. However, since PC is a non-crystalline polymer and PET is a crystalline polymer, the actual compatibility between the two is not ideal. At the same time, due to the active groups (such as carboxyl and hydroxyl) and the residual catalysts during the synthesis of PC and PET after contact, the resins are easily degraded during production or use, resulting in poor thermal stability, poor appearance, and weakened mechanical properties of the product.

[0003] In order to improve the compatibility between the two, the existing technology often introduces two-phase compatibilizers into the product. However, in order to make the PC / PET alloy material meet the use requirements, mineral fillers are often further introduced into the product to improve the rigidity. However, this type of filler-containing alloy material can no longer achieve mutual compatibility of the inorganic phase-organic crystalline phase-organic non-crystalline phase of the product using traditional two-phase compatibilizers. In fact, the comprehensive performance of the product is further deteriorated due to the introduction of the inorganic phase. In addition, many traditional small molecule or polymer compatibilizers mainly rely on active group cross-linking to achieve compatibility, so they are relatively active but not very stable, and cannot improve the thermal stability of the product. Summary of the invention

[0004] Based on the defects of the prior art, the purpose of the present invention is to provide a PC / PET alloy material. The product introduces talcum powder with a specific pH into the base resin as a reinforcing filler, and compounded with a special reinforcing polymer as a modified component. The component can not only improve the overall compatibility of the product, but also inhibit the reactivity of the base resin, improve the heat resistance stability and appearance of the product, and assist talcum powder as a rigidity enhancer to improve the rigidity performance of the product while ensuring sufficient toughness. The comprehensive performance of the product is excellent.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] A PC / PET alloy material comprises the following components in parts by weight:

[0007] 40-70 parts of PC resin, 15-30 parts of PET resin, 10-20 parts of talc, 2-5 parts of reinforcing polymer;

[0008] The pH of the talc is 6 to 8.5;

[0009] The reinforcing polymer is acrylonitrile-styrene-acrylic acid copolymer, and the mass content of acrylic acid is 6-15%.

[0010] In addition to the differences in crystallinity and non-crystallization, the main reason why PC and PET are prone to "1+1<2" performance weakening after mixing is that both contain highly active groups. Once compounded, the performance of the products may deteriorate rapidly. At the same time, after the alloy material is reinforced with mineral fillers, in addition to the introduction of the third incompatible phase, there are also some active hydroxyl groups on the surface of the mineral fillers, which accelerate the degradation of the resin.

[0011] For this reason, the inventor takes into account the mechanism of action of three key components, and critically introduces a reinforcing polymer acrylonitrile-styrene-acrylic acid copolymer as a compounding component, and introduces talcum powder containing a specific pH value at the same time, under the compounding formula, it is not only fully compatible with PC and PET, but also improves the compatibility of the two phases on the one hand, and can also play a certain passivation protection effect on the matrix resin at the same time, and acrylonitrile-styrene-acrylic acid copolymer can also bring higher rigidity to the product, so the reinforcing polymer also belongs to the rigidity enhancer of the product. Meanwhile, talcum powder has a better rigidity enhancement effect compared to other mineral components, and its main component is stable magnesium silicate, so its composition will not have too many changes with the acidity and alkalinity of pH, under this premise, the talcum powder under the pH value can not affect the protective effect of acrylonitrile-styrene-acrylic acid copolymer for the matrix resin after introduction, and can even synergistically strengthen this protective effect, and finally realize the high heat resistance stability and good appearance of the product. The system, under the collocation of the three, can also take into account the realization of ideal toughness and rigidity requirements.

[0012] However, the selection and ratio of acrylonitrile-styrene-acrylic acid copolymer and talcum powder need to be carefully considered. In addition to the rigidity of the product, the passivation protection effect of the two on PC resin is limited. If the acrylic acid content in acrylonitrile-styrene-acrylic acid copolymer is too high, or the pH selection of talcum powder is inappropriate, the base resin may also degrade, and the performance may even be worse than that of conventional talc-filled PC / PET alloy materials.

[0013] Preferably, the pH of the talc is determined by electrode testing, standard number HJ 1147-2020.

[0014] Preferably, the acrylic acid mass content of the acrylonitrile-styrene-acrylic acid copolymer is calculated based on the acid value, which is measured using the KOH titration method according to ASTM D 1386-2015. The calculation method is as follows: acrylic acid mass content = acid value / amount of KOH substance * amount of acrylic acid substance.

[0015] Preferably, the weight proportion of the PC resin is 40 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts or any two of the range values; the weight proportion of the PET resin is 15 parts, 20 parts, 25 parts, 30 parts or any two of the range values; the weight proportion of the talc is 10 parts, 15 parts, 20 parts or any two of the range values; the weight proportion of the reinforcing polymer is 2 parts, 3 parts, 4 parts, 5 parts or any two of the range values.

[0016] Preferably, the pH value of the talc is in the range of one or any two of 6, 6.5, 7, 7.5, 8, 8.5;

[0017] More preferably, the pH value of the talc is 6.5-7.

[0018] As mentioned above, the pH change of talcum powder has a certain influence on the protective effect of PC resin on the enhanced polymer. When the pH of talcum powder is maintained within the above range, the chemical passivity and thermal passivity of PC resin in the product are the highest, and the overall performance of the product is the best.

[0019] More preferably, the pH of the talc can be adjusted by soaking in a glacial acetic acid solution for different periods of time, and those skilled in the art can also choose other operating methods to adjust the pH value of the talc according to actual conditions, as long as it does not affect the final performance results of the product.

[0020] Preferably, the particle size D50 of the talc powder is 4-8 μm.

[0021] Preferably, the particle size D50 of the talc powder is 5-7 μm.

[0022] The particle size D50 of the talcum powder is determined by a particle size analyzer.

[0023] The inventors have found through screening that when the particle size of talc is preferably within the above range, the comprehensive performance of the product is better.

[0024] Preferably, the acrylic acid mass content of the acrylonitrile-styrene-acrylic acid copolymer is in the range of 6%, 8%, 10%, 12%, 15% or any two of them;

[0025] More preferably, the acrylic acid mass content of the acrylonitrile-styrene-acrylic acid copolymer is 8-12%.

[0026] The acrylic acid segment in acrylonitrile-styrene-acrylic acid copolymer has a great influence on the overall acid-base environment of the product. In addition to maintaining the compatibility of each phase, when the proportion of acrylic acid is within the above range, its passivation protection effect on the base resin is the best.

[0027] Preferably, the PC resin is a phosgene-processed PC resin;

[0028] Preferably, in the PC / PET alloy material, the total mass content of PC resin and PET resin is ≥50wt%.

[0029] Preferably, the PC resin has a melt index of 10 to 35 g / 10 min at 300° C. and 1.2 kg load as tested in accordance with IS0 1133-2012.

[0030] Preferably, the intrinsic viscosity of the PET resin at 25° C. is 0.8 to 0.9 dL / g;

[0031] The intrinsic viscosity of the PET resin is tested according to ASTM D4603-2011.

[0032] Preferably, the mass ratio of the talc powder to the reinforcing polymer is (4-5):1.

[0033] As mentioned above, in addition to being a rigidity enhancer to improve the rigidity of the product, the reinforcing polymer is also a key substance for balancing the compatibility and reactivity of talc. When the addition amounts of the reinforcing polymer and talc are maintained within the above range, the reinforcing polymer has the highest degree of synergistic rigidity enhancement, compatibility and improvement of the overall reaction inertness of the product for talc.

[0034] Preferably, the PC / PET alloy material also includes 2 to 5 parts of a toughening agent, 0.1 to 1 part of an antioxidant, and 0.1 to 1 part of a lubricant.

[0035] In order to expand the practicality of the product, in addition to the key components, technical personnel in this field can also introduce additional additives according to actual needs to give the product more properties. For example, in order to make the product have a certain toughness while having high rigidity, technical personnel in this field can introduce a certain amount of toughening agent into the product; in order to improve the environmental stability of the product, technical personnel in this field can introduce a certain amount of antioxidant into the product; in order to improve the processing performance of the product, technical personnel in this field can introduce a certain amount of lubricant into the product. It should be noted that the above-mentioned ingredients that can be introduced are not limitations on the product components. Technical personnel in this field can also introduce other ingredients not mentioned in the present invention according to other requirements without affecting the key performance of the product.

[0036] More preferably, the toughening agent is a silicon-acrylic toughening agent;

[0037] More preferably, the antioxidant is at least one of a hindered phenol antioxidant and a phosphite antioxidant;

[0038] More preferably, the lubricant is at least one of a stearate lubricant and a silicone lubricant.

[0039] Another object of the present invention is to provide a method for preparing the PC / PET alloy material, comprising the following steps:

[0040] The components except talcum powder are mixed uniformly, and then put into a screw extruder with the talcum powder for melt extrusion to obtain the PC / PET alloy material.

[0041] The preparation method of the PC / PET alloy material of the present invention has simple operation steps and can realize industrial large-scale production.

[0042] Preferably, the melt extrusion temperature range of the screw extruder is 200-280° C., the screw aspect ratio is (38-42):1, and the screw speed is 400-500 rpm.

[0043] Another object of the present invention is to provide application of the PC / PET alloy material in the preparation of automobile parts.

[0044] Preferably, the automobile parts include a spoiler, an antenna cover, a laser radar cover and an electric rear wing.

[0045] The PC / PET alloy material of the present invention has high rigidity characteristics and is very suitable for automotive parts with high rigidity requirements. In this field, due to the requirements of the working environment, the product must also have sufficient thermal stability and should also be aesthetically pleasing without obvious appearance defects. Under the interaction of the various components of the product of the present invention, the product has both heat resistance and good appearance, and therefore fully meets the requirements of this type of application.

[0046] The beneficial effect of the present invention is that the present invention provides a PC / PET alloy material, which introduces talcum powder with a specific pH value into a base resin as a reinforcing filler, and compounded with a special reinforcing polymer as a modified component. The component can not only improve the overall compatibility of the product, but also inhibit the reactivity of the base resin, improve the heat resistance stability and appearance of the product, and assist the talcum powder as a rigidity enhancer to improve the rigidity performance of the product while ensuring sufficient toughness. The comprehensive performance of the product is excellent. DETAILED DESCRIPTION

[0047] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.

[0048] Examples 1 to 20

[0049] The embodiments of the PC / PET alloy material and the preparation method thereof of the present invention, the composition of the PC / PET alloy material is shown in Table 1.

[0050] The preparation method of the PC / PET alloy material comprises the following steps:

[0051] The components except talcum powder were mixed uniformly for 2 minutes, and then the obtained mixture and talcum powder (added from a side feeding port) were melted and granulated to obtain the PC / PET alloy material.

[0052] The melting is carried out in a twin-screw extruder, and the temperature of each zone in the twin-screw extruder is set to: zone one temperature is 200°C, zone two temperature is 220°C, zone three temperature is 230°C, zone four temperature is 240°C, zone five temperature is 240°C, zone six temperature is 250°C, zone seven temperature is 260°C, zone eight temperature is 260°C, zone nine temperature is 260°C, zone ten temperature is 280°C, the screw speed of the twin-screw extruder is 450rpm, and the aspect ratio is 40:1.

[0053] Comparative Examples 1 to 7

[0054] The difference between the comparative examples and the embodiments is only in the types and proportions of components, as shown in Table 2.

[0055] Among the components described in each embodiment and comparative example,

[0056] The PC resin 1 is IR1900 produced by Formosa Chemical Corporation, and has a melt index of 20 g / 10 min at 300° C. and 1.2 kg;

[0057] The PC resin 2 is PC H-3000F produced by Mitsubishi Chemical, and has a melt index of 30 g / 10 min at 300° C. and 1.2 kg;

[0058] The PET resin 1 is CB-608S produced by Shanghai Yuanfang, and has an intrinsic viscosity of 0.865 dL / g at 25°C;

[0059] The PET resin 2 is BG80 produced by Yizheng Chemical Fiber, and has an intrinsic viscosity of 0.8 dL / g at 25°C;

[0060] The PET resin 3 is EP901 produced by Yizheng Chemical Fiber, and its intrinsic viscosity at 25°C is 0.9 dL / g;

[0061] The talcum powder 1 is homemade, and the preparation method is as follows: weigh 100mL of glacial acetic acid and put it into a polytetrafluoroethylene beaker, add water to adjust the pH value of the solution to 5.0, weigh 20g of talcum powder and put it into a polytetrafluoroethylene beaker, and by controlling the soaking time of talcum powder in glacial acetic acid, the pH value of the surface of the treated talcum powder can be adjusted. The longer the soaking time, the closer the pH of the talcum powder is to the solution pH. Soak with magnetic stirring at room temperature and then filter by suction, and put the talcum powder into an 80°C oven to dry for 120 minutes to obtain talcum powder 1, with a pH of 7;

[0062] The talcum powder 2 is homemade, and the difference between the preparation method and the talcum powder 1 is only that the soaking time is adjusted to make the pH value 6.5;

[0063] The talcum powder 3 is homemade, and the difference between the preparation method and the talcum powder 1 is only that the soaking time is adjusted to make the pH value 6;

[0064] The talcum powder 4 is homemade, and the difference between the preparation method and the talcum powder 1 is only that the soaking time is adjusted to make the pH value 8.5;

[0065] The talcum powder 5 is homemade, and the difference between the preparation method and the talcum powder 1 is only that the soaking time is adjusted to make the pH value 5.2;

[0066] The talcum powder R is derived from the product screened by SDC-9489 produced by Liaoning Aihai Yimi Mining Co., Ltd., and the particle size D50 after screening is 6 μm and the pH is 9.2;

[0067] The talcum powder 6 is homemade, and the difference in preparation method from the talcum powder 1 is only that the particle size after screening is different, and the talcum powder R is replaced by a product from the same source with a particle size D50=5 μm after screening;

[0068] The talcum powder 7 is homemade, and the difference in preparation method from the talcum powder 1 is only that the particle size after screening is different, and the talcum powder R is replaced by a product from the same source with a particle size D50=4 μm after screening;

[0069] The talcum powder 8 is homemade, and the difference in preparation method from the talcum powder 1 is only that the particle size after screening is different, and the talcum powder R is replaced by a product from the same source with a particle size D50=8 μm after screening;

[0070] The reinforcing polymer 1 is acrylonitrile-styrene-acrylic acid copolymer, RAS-610 produced by Jiaxing Huawen Chemical, with an acrylic acid content of 10%;

[0071] The reinforcing polymer 2 is acrylonitrile-styrene-acrylic acid copolymer, RAS-603 produced by Jiaxing Huawen Chemical, with an acrylic acid content of 3%;

[0072] The reinforcing polymer 3 is acrylonitrile-styrene-acrylic acid copolymer, RAS-606 produced by Jiaxing Huawen Chemical, with an acrylic acid content of 6%;

[0073] The reinforcing polymer 4 is acrylonitrile-styrene-acrylic acid copolymer, RAS-608 produced by Jiaxing Huawen Chemical, with an acrylic acid content of 8%;

[0074] The reinforcing polymer 5 is acrylonitrile-styrene-acrylic acid copolymer, RAS-612 produced by Jiaxing Huawen Chemical, with an acrylic acid content of 12%;

[0075] The reinforcing polymer 6 is acrylonitrile-styrene-acrylic acid copolymer, RAS-615 produced by Jiaxing Huawen Chemical, with an acrylic acid content of 15%;

[0076] The reinforcing polymer 7 is acrylonitrile-styrene-acrylic acid copolymer, RAS-620 produced by Jiaxing Huawen Chemical, with an acrylic acid content of 20%;

[0077] The PC / PET alloy compatibilizer is PTW produced by DuPont Company of the United States;

[0078] The toughening agent is S2001 produced by Mitsubishi Rayon, a silicon-acrylate type toughening agent;

[0079] The antioxidant is a mixture of commercially available hindered phenol antioxidant and phosphite antioxidant in a ratio of 1:2;

[0080] The lubricant is a commercially available stearate lubricant.

[0081] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.

[0082] Table 1

[0083]

[0084]

[0085] Table 2

[0086]

[0087]

[0088] Effect Example 1

[0089] In order to verify the performance of the PC / PET alloy material of the present invention, the products prepared in each embodiment and comparative example were subjected to the following performance tests, and the specific steps are as follows:

[0090] (1) Impact strength test: tested according to ISO 180-2019 method, pendulum 5.5J, V-notch;

[0091] (2) TGA loss rate test (thermal stability test): the sample was heated at 30°C at 20K (Fahrenheit) / min to 700°C in a nitrogen atmosphere, and kept at 270°C for 60 min. The TGA loss rate was the mass loss of the sample from the initial state to the end of the heat preservation / the initial mass of the sample × 100%;

[0092] (3) Appearance test: The sample is injection molded into a 356*10*3 mm sample at 270°C. The sample is then photographed using a camera software and the total amount of material flowers / silver threads on the sample surface is counted using a statistical software. If the area of ​​the material flowers / silver threads is less than 5%, it is rated as Level 1; 5-10% is rated as Level 2; 10-30% is rated as Level 3; 30-50% is rated as Level 4; and more than 50% is rated as Level 5.

[0093] The test results are shown in Tables 3 and 4.

[0094] Table 3

[0095]

[0096] Table 4

[0097] Test items Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 <![CDATA[Impact strength (kJ / m 2 )]]> 10 4 5 6 5 10 8 TGA loss rate (%) 0.45 0.85 0.64 0.76 0.73 0.58 0.61 Appearance 2 5 3 4 4 3 3

[0098] It can be seen from Tables 3 and 4 that the PC / PET alloy material of the present invention has ideal heat resistance stability and appearance performance, the appearance grade can reach 1-2, and the TGA loss rate can reach less than 0.3%. At the same time, due to the compound use of talcum powder and reinforcing polymer, the product has a notched impact strength of at least 10kJ / m 2As above, the toughness is high, and the comprehensive performance is far better than the conventional talcum powder reinforced PC / PET alloy material described in Comparative Example 1 prepared by compounding with conventional compatibilizers. In the product described in the present invention, the type of talcum powder and the type of reinforcing polymer will have a great influence on the toughness performance, heat resistance stability and appearance of the product. The main reason is that the selection of the two is about the thermal inertness and chemical inertness of the PC resin in the product. It can be seen from Example 3, Examples 8 to 10 and Comparative Examples 4 and 5 that the existing conventional talcum powder cannot be applied to the product system described in the present invention. It will increase the degradation activity of the PC resin, resulting in a significant decrease in the performance of the product. As the pH of the talcum powder decreases, the degree of resin degradation of the product becomes lower, and the performance gradually improves. When the pH of the talcum powder reaches 6.5 to 7, this weakly acidic talcum powder improves the performance of the product. The increase is the highest. If the pH of talcum powder is further reduced to below 6, as shown in Comparative Example 4, the performance of the product will also be greatly reduced. Similarly, the only difference between the products of Example 3, Examples 14 to 17 and Comparative Examples 6 and 7 is that the acrylic acid content in the reinforcing polymer is different. When the acrylic acid content is low, it cannot effectively play a passivation effect on the PC resin. The product has poor heat stability and poor appearance, and the toughness is also poor due to the degradation of the PC resin. With the increase of the acrylic acid content, especially when it reaches 8 to 12%, the comprehensive performance of the product is significantly improved. If the acrylic acid content is too much, as shown in Comparative Example 7, the performance of the product will be reduced to an unqualified level. In addition, according to Examples 3, Examples 18 to 20 and Comparative Example 2, it can be seen that within a certain range, the reinforcing polymer has a compatibility effect on talcum powder. As the amount of talcum powder added increases, the improvement effect of the reinforcing polymer on talcum powder gradually decreases, especially when the amount of talcum powder added exceeds the formula limit of the product described in the present invention, the reinforcing polymer can no longer suppress the compatibility problem caused by talcum powder, and the corresponding Comparative Example 2 product appearance and heat stability do not meet the requirements. On the other hand, as shown in Comparative Example 3, if the reinforcing polymer is added too much, the overall performance of the product will also decline. The pH of the talc in the products of Example 3 and Examples 11 to 13 is the same, and the only difference is the particle size. It can be seen that when the size of the talc is selected in the range of 5 to 7 μm, the comprehensive performance of the product is better.

[0099] In addition, the flexural modulus of the products of each embodiment was tested according to ISO178-2019. The results showed that each product could reach more than 3600 MPa, while the product of Comparative Example 1 which did not use the reinforcing polymer had only 3300 MPa under the same test, which fully demonstrated that the reinforcing polymer as a modifying ingredient can also assist talcum powder as a rigidity enhancer to improve the rigidity performance of the product while ensuring sufficient toughness.

[0100] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A PC / PET alloy material, characterized in that: The composition comprises the following components in parts by weight: 40-70 parts of PC resin, 15-30 parts of PET resin, 10-20 parts of talc, 2-5 parts of reinforcing polymer; The pH value of the talcum powder is 6-8.5; The reinforcing polymer is acrylonitrile-styrene-acrylic acid copolymer, and the mass content of acrylic acid is 6-15%; the particle size D50 of the talc powder is 4-8 μm.

2. The PC / PET alloy material according to claim 1, characterized in that: The PC resin has a melt index of 10-30 g / 10 min at 300° C. and 1.2 kg load as tested in accordance with IS0 1133-2012.

3. The PC / PET alloy material according to claim 1, characterized in that: The mass ratio of the talc powder to the reinforcing polymer is (4-5):

1.

4. The PC / PET alloy material according to claim 1, characterized in that: The components of the PC / PET alloy material also include 2-5 parts of a toughening agent, 0.1-1 parts of an antioxidant and 0.1-1 parts of a lubricant.

5. The PC / PET alloy material as claimed in claim 4, characterized in that: The toughening agent is a silicon-acrylic toughening agent; the antioxidant is at least one of a hindered phenol antioxidant and a phosphite antioxidant; and the lubricant is at least one of a stearate lubricant and a silicone lubricant.

6. The method for preparing the PC / PET alloy material according to any one of claims 1 to 5, characterized in that: The following steps are involved: The components except talcum powder are mixed uniformly, and then put into a screw extruder with the talcum powder for melt extrusion to obtain the PC / PET alloy material.

7. Use of the PC / PET alloy material according to any one of claims 1 to 5 in the preparation of automotive parts.

8. The use according to claim 7, characterized in that The automotive parts include spoilers, antenna covers, lidar covers and electric rear wings.

Citation Information

Patent Citations

  • Flame retardant resin composition

    CN101759990A

  • Anti-ultraviolet heat-resistant PET (polyethylene terephthalate) film material as well as preparation method and application thereof

    CN117209979A

  • Talcum powder filled PC / ABS alloy material as well as preparation method and application thereof

    CN117700973A

  • Talc-filled polycarbonate compositions

    EP3502183A1

  • Polyethylene terephthalate-made sheet and polyethylene terephthalate-made heat-resistant container

    JP2018127554A